Quick Response (QR) Code’s Use and Students’ Motivation In English Online Learning: A Correlational Study - Malik, Zulfikri; Pramesti, Widya Ayu; Chasanah, Uswatun (ICONELT, 2022)
The application of Quick Response (QR) code as teaching media has become growing favored. Previous studies demonstrated that it can improve the student’s motivation in learning. Hence, this research aims to find and demonstrate the correlation between using Quick Response (QR) Code as assisted language media and student’s motivation in English online learning. The type of this research is quantitative research with a descriptive correlational design. The research population is the 5th semester students of English Language Education Department UIN Sunan Ampel Surabaya. The sample used is 30 students with techniques Random Sampling. The data have been collected by using questionnaire consisting of 12 questions on using Quick Response (QR) Code as assisted language learning and 12 questions on students’ motivation in English online learning. After gaining the data, the data were analyzed by using Pearson Product Moment on SPSS software version 25. Correlation coefficient obtained in this study was 0.807 with a significance level of 0.00 (p <0.05). It can be concluded that there is a positive and significant correlation between using Quick Response (QR) Code as assisted language media and students’ motivation in English online learning.